BreathCarer: Informal carers of patients with chronic breathlessness: a mixed-methods systematic review of burden, needs, coping, and support interventions - Saskia Blütgen; Anne Pralong; Carolin Wilharm; Yvonne Eisenmann; Raymond Voltz; Steffen T. Simon (BMC Palliative Care)
Abstract Background Breathlessness is a common symptom in chronic and advanced diseases, and it poses a significant burden to patients and to their informal carers. They play a crucial role in sustainable care for patients living with breathlessness, but their challenges and needs are often neglected. Objective To provide a systematic overview of the literature on the burden, needs, coping and use of healthcare and social services by carers of patients suffering from chronic breathlessness due to any life-limiting disease. Design A mixed-methods systematic review (PROSPERO CRD42022312989). Data sources Medline, CENTRAL, PsycINFO, and CINAHL were searched and complemented with forward and backward searches and expert consultation. Review methods The mixed-methods review included any study on burden, needs and coping among carers of patients with breathlessness published from the inception of the databases until July 2023. A narrative analysis of the quantitative results and a pragmatic meta-aggregation of the qualitative findings were performed, followed by a mixed-methods convergent segregated approach. Findings A total of 53 studies with 4,849 carers were included. Breathlessness is highly burdensome for carers who live with and care for patients or for those who do not live with the patients and care for them. Breathlessness is a significant risk factor for high carers’ burden, contributing to deteriorating physical and mental health among carers and creating an urgent need for external support. A major challenge is the sense of being trapped in a state of constant alertness and anxiety, centred around managing the patient's breathlessness. Carers bear substantial emotional burden due to uncertainty, sleep disturbances, and social isolation, which leads to severe psychological distress. Their unmet needs for professional guidance, self-management strategies, and social interaction are high. While supportive interventions, such as specialized services and multidisciplinary approaches, can alleviate some of the burden, there remains a lack of targeted interventions specifically designed for carers. Conclusions This review highlights the substantial burden associated with caring for patients with chronic breathlessness, the unmet needs of carers and the lack of supportive care structures, leaving them with little option but to accept the situation.